Diagnosis and management of gastrointestinal complications in adult cancer patients: 2017 updated evidence-based guidelines of the Infectious Diseases Working Party (AGIHO) of the German Society of Hematology and Medical Oncology (DGHO) - Schmidt-Hieber, Martin; Buchheidt, Dieter (Annals of hematology, 2018)
Cancer patients frequently suffer from gastrointestinal complications. In this manuscript, we update our 2013 guideline on the diagnosis and management of gastrointestinal complications in adult cancer patients by the Infectious Diseases Working Party (AGIHO) of the German Society of Hematology and Medical Oncology (DGHO). An expert group was put together by the AGIHO to update the existing guideline. For each sub-topic, a literature search was performed in PubMed, Medline, and Cochrane databases, and strengths of recommendation and the quality of the published evidence for major therapeutic strategies were categorized using the 2015 European Society for Clinical Microbiology and Infectious Diseases (ESCMID) criteria. Final recommendations were approved by the AGIHO plenary conference. Recommendations were made with respect to non-infectious and infectious gastrointestinal complications. Strengths of recommendation and levels of evidence are presented. A multidisciplinary approach to the diagnosis and management of gastrointestinal complications in cancer patients is mandatory. Evidence-based recommendations are provided in this updated guideline.